Hedonic and pragmatic halo effects at early stages of User Experience. Issue 109 (January 2018) - Minge, Michael; Thüring, Manfred
Highlights: We examine changes in product-related perceptions and emotions at early stages and for short-time usage. Before any interaction takes place, the visual aesthetics of the device influences perceived usability. Already after a short period of interacting with the product, this influence vanishes and system usability starts affecting perceived visual attractiveness and emotions. To account for both influences, we distinguish between a hedonic halo effect ('beautiful is usable') and a pragmatic halo effect ('usable gets beautiful'). Based on the results, we propose that a heuristic may bias ratings of usability in the beginning while emotions may bias ratings of aesthetics at later stages. Abstract: User Experience (UX) has emerged as a comprehensive concept which provides a holistic perspective on users' interaction with technology. This concept can be characterized as a multidimensional phenomenon that comprises both, the perception of different product qualities as well as emotions that arise while using a product. The interrelations of these components are described in the 'Component Model of User Experience' (CUE model), which serves as the theoretical basis for our experiment. UX can be investigated in different phases of usage. In our experiment, we examined product perceptions and emotions in early phases and for short-time usage. Sixty participants employed different versions of mobile digital audio players which were systematically varied with respect to visual aesthetics and usability. Essential aspects of UX, i.e., perceptions of visual attractiveness and usability, as well as emotional responses were measured at three stages: Before interacting with the device, after an exploration (2 min) and after working with the system for a short time (15 min) to solve a given set of tasks. Data was analysed using a 2 × 2 × 3 mixed MANCOVA. The results of the experiment show that influences of visual aesthetics and of usability on quality perceptions as well as emotions change during these early stages. Moreover, evidence for two different halo effects was found: On the one hand, visual aesthetics influenced perceived usability in the beginning. On the other hand, the usability of the device impacted the perceived visual attractiveness and emotional responses at later stages. To account for these findings, we suggest to distinguish a hedonic halo effect from a pragmatic one. Based on the results for both effects, we propose that two mechanisms may be responsible for the effects during short-time usage, one of them being cognitive in nature, the other emotional.